The effect of non-pharmacological interventions on bone health among patients with low bone mass: a systematic review and meta-analysis - Na, Xiaona; Yang, Yucheng; Yang, Huanhuan; Chen, Zekun; Qu, Xiaochen; Zhang, Jian; Chen, Mo; Wang, Dantong; Breuille, Denis; Yu, Kai; Zhao, Ai; Li, Zhihui (Frontiers in Endocrinology, 2025)
Background and objectiveLow bone mass represents a critical period for “watchful waiting” interventions to prevent osteoporosis. This systematic review provides a comprehensive overview of non-pharmacological interventions for patients with low bone mass.MethodsWe included randomized controlled trials (RCTs) investigating the efficacy of non-pharmacological interventions for improving bone health outcomes in participants with low bone mass. Publications were collected from three databases. A meta-analysis was performed for outcomes reported in three or more articles, with changes in outcomes expressed as mean differences (MD) or standardized mean differences (SMD) with 95% confidence intervals (CIs).ResultsA total of 26 eligible articles were included. Exercise interventions increased serum osteocalcin levels (SMD = 1.26, 95% CI: 0.22–2.31) compared to the control group. Narrative synthesis of studies showed a protective effect of exercise on lumbar spine and femoral neck BMD. For nutrition interventions, polyphenol extracts showed efficacy in improving lumbar spine BMD. The results of collagen supplements were inconsistent, and the effects of micronutrients were limited.ConclusionIn conclusion, more evidence from RCTs, particularly those investigating comprehensive lifestyle interventions and tailored prevention for moderate and severe low bone mass, especially among older men, is necessary.